The Well-Being of Student Veterans: A Feasibility Study Using the Well-Being Inventory in the Academic Setting - Madisen O'Laughlin; Mona Pearl Treyball; Sophia Centi; Bryan McNair; Lori Trego (The Ohio State University Libraries, 2023)
Background: Veterans are using the Post 9/11 GI Bill benefits for post-secondary education more than ever. Military life experiences, including combat deployments and the visible and invisible wounds from their time in the service, affect Student Veterans' (SV) well-being and may complicate their transition to a student role and the road to academic success. Aim: The aim of this pilot study was to investigate the educational well-being among SV. A secondary aim was to determine the feasibility of measuring well-being in SV with the Well-Being Inventory (WBI), a validated tool that measures four domains of well-being in veterans: (1) vocation, (2) health, (3) financial, and (4) social well-being. Methods: In this cross-sectional pilot study, the WBI was completed by SV (N = 58) via an electronic survey platform. The status, functioning, and satisfaction of the domains of well-being were scored. Correlational statistics were calculated to detect relationships of educational well-being with vocation, work, health, financial, and social well-being domains. Results: Educational well-being was associated with vocation, work, health, and social well-being. SV exhibited the least well-being in the financial and health domains. Conclusions: Academic settings that offer support to SV in relation to their vocation, work, health, and social well-being may enhance SV academic success.